T cell and monocyte activation in concert with hematopoietic stem cell interactions shapes the post-allogeneic transplant immune landscape in poor graft function - Prabahran, Ashvind; Wu, Zhijie; Gao, Shouguo; Morgan, Huw; Holzwart, Nicholas; Ludford-Menting, Mandy; Rawicki, Mayani; Klass, Jessica; Koo, Ray-Mun; Wilson, Clarissa; Blombery, Piers; Tan, Chin Wee; et al. (Frontiers in Immunology, 2026)
IntroductionPost-allogeneic stem cell transplantation (alloSCT) can be complicated by poor graft function (PGF), a life-threatening condition characterized by complete donor chimerism alongside persistent multilineage cytopenias. PGF significantly increases the risk of bleeding, infection, and transfusion dependence. The cellular changes during hematopoiesis post-alloSCT, particularly in PGF, remain poorly defined.MethodsTo evaluate the immune and hematopoietic reconstitution and dysfunction post-alloSCT, with a focus on PGF, we applied a comprehensive suite of histological, immunological, and molecular biological techniques to bone marrow (BM) and peripheral blood samples from patients with PGF, good graft function (GGF), and healthy donors (HDs).ResultsBy approximately 100 days post-alloSCT, patients demonstrated T cell oligoclonality, activation, and exhaustion compared to HDs. BM nucleated cells, particularly monocytes, exhibited increased activation and IFN-g response post-alloSCT compared to those of HDs. Moreover, cell-cell interactions between immune cells and hematopoietic stem and progenitor cells were notably enhanced post-alloSCT. While most inflammatory changes were present in both PGF and GGF, they were more pronounced in PGF.DiscussionOur results demonstrate a hyper-inflamed post-alloSCT environment involving both innate (monocytes) and adaptive (T cells) immune responses and their active interactions, more in PGF, highlighting that immune modulation may serve as an alternative or adjunctive therapeutic approach for PGF.